High-performance zinc-iodine battery diaphragm as well as modification process and application thereof

The high-performance zinc-iodine battery separator prepared through the modification process uses the combination of covalent organic frame material and graphene to solve the problems of excessive pore size and insufficient cation permeability of traditional separators, significantly improving the performance and circulation of zinc-iodine batteries. Lifetime, achieving efficient conductivity and safety.

CN119253190AActive Publication Date: 2025-01-03HAINAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411288028.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-03
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The traditional zinc-iodine battery separator has a large pore size, resulting in a serious shuttle effect of multiple iodides, and the cation selective permeability membrane structure is poorly enclosed, affecting the conductivity of zinc ions and battery performance.

Method used

High-performance zinc-iodine cell separators were prepared by modification process, through 2,4,6-tris(4-aminophenyl)triazine and 4,4',4"-(1,3,5-triazine-2, 4,6-triyl)tribenzaldehyde reacts with pyruvate to form a covalent organic frame material and mixes it with graphene to form a filter membrane to optimize pore size and conductivity.

Benefits of technology

It significantly improves the discharge capacity, Coulomb efficiency and cycle life of zinc-iodine batteries, enhances the conductivity and safety of the diaphragm, and provides stable Coulomb efficiency for up to 800 hours and significant application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253190A_ABST
    Figure CN119253190A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance zinc-iodine battery diaphragm as well as a modification process and application thereof. The modification process comprises the following steps: reacting 2, 4, 6-tri (4-aminophenyl) triazine and 4, 4 ', 4' '-(1, 3, 5-triazine-2, 4, 6-triyl) tribenzaldehyde with pyruvic acid in a solvent, quickly freezing at a low temperature, circularly degassing, reacting at a high temperature to obtain a yellow precipitate, and washing and drying the precipitate to obtain the covalent organic framework material. And applying the covalent organic framework material and graphene to the glass fiber diaphragm through a suction filtration method to obtain the zinc-iodine battery diaphragm. The zinc-iodine battery diaphragm prepared by the invention has excellent hydrophilicity and proper aperture, and can promote rapid transmission of Zn < 2 + >; and a small pore channel can effectively hinder shuttling of the polyiodide. Besides, carboxylic acid groups rich in the diaphragm can form a chemically stable interface on the surface of the diaphragm, the ion permeation speed is reduced, the conductivity of the diaphragm is improved, and an unexpected reaction between iodide ions and zinc ions is effectively prevented, so that the cycle life of the battery is prolonged, and the safety of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to a high-performance zinc-iodine battery separator and a modification process and application thereof. Background Art

[0002] The use of traditional fossil energy has brought about energy crises and serious greenhouse effect problems, so countries have proposed goals for carbon emission reduction and clean energy transformation. Among these goals, the development of renewable energy is considered to be one of the key ways. However, due to the large volatility of renewable energy grids, there are certain challenges in practical applications. In order to achieve the goals of carbon emission reduction and clean energy transformation, it is necessary to develop efficient energy storage technology. In this way, it can not only solve the problems caused by the volatility of renewable energy, but also effectively promote the development of clean energy and further achieve carbon emission reduction goals.

[0003] Traditional lithium-ion batteries are widely used in digital electronic products and new energy vehicles, but they have safety issues and high costs. Although traditional lead-acid batteries are low-cost and safe, their low volume energy density, poor cycle life, environmental pollution and other issues have affected their application and development in the field of energy storage. Therefore, there is an urgent need to develop a new energy storage battery system with low cost, high safety and long life to support the country's strategic goals of "carbon peak" and "carbon neutrality" and support the development of renewable energy. Renewable energy has the problem of high volatility, so it is crucial to develop efficient energy storage technology to balance grid fluctuations. The research and development of new energy storage battery systems will help solve the problems of traditional batteries and promote the realization of clean energy transformation.

[0004] Aqueous secondary battery systems have many advantages, including high safety, low cost, green environmental protection, and low production conditions. Although its electrochemical window is not as good as that of organic electrolyte systems, it has higher ionic conductivity, which can achieve higher power density. Therefore, aqueous secondary batteries show broad application prospects and strong competitiveness in large-scale electrochemical energy storage systems.

[0005] Aqueous secondary batteries mainly include monovalent alkali metal ion batteries and high-valent metal ion batteries. High-valent metal ion batteries have a moderate potential, which is conducive to alleviating side reactions in aqueous electrolytes. Zinc, as an element, has the advantages of high reserves, low cost, and strong corrosion resistance. The zinc negative electrode has a high theoretical specific capacity and good electroplating / stripping reversibility. Therefore, considering the characteristics of the zinc element, it can be considered that zinc has development potential and broad application prospects in aqueous secondary batteries.

[0006] Zinc-iodine secondary batteries using aqueous zinc salt solutions have many advantages, including fast reaction speed, good reversibility, and high energy / power density.3- The intermediate state will lead to serious shuttle effect. In order to solve this problem, measures need to be taken to improve the battery's discharge capacity, coulombic efficiency and cycle life.

[0007] The glass fiber separator commonly used in traditional zinc ion battery research has a problem that the pore size is large, which makes it difficult to effectively block the phenomenon of polyiodide shuttling. In addition, the closure of the cation selective permeable membrane structure also leads to low conductivity of zinc ions, thus affecting the performance of the battery. Therefore, it is necessary to design a separator that can quickly conduct Zn 2+ The key to solving the above problems is to develop an efficient diaphragm that can effectively block the shuttle of multiple iodides. By improving the design of the diaphragm and the selection of materials, the performance of zinc-ion batteries can be significantly improved, promoting their application in the field of energy storage.

[0008] Therefore, one of the current challenges in the field of zinc-iodine batteries is to develop a 3- Barrier efficiency and high Zn 2+ The integrated thin-layer diaphragm with high transmittance can improve the discharge capacity, coulombic efficiency and rate performance of zinc-iodine batteries. Solving this problem is crucial to further improve the performance of zinc-iodine batteries. Summary of the invention

[0009] In view of this, the present invention proposes a high-performance zinc-iodine battery separator and a modification process and application thereof.

[0010] The technical solution of the present invention is achieved in this way:

[0011] A modification process for a high-performance zinc-iodine battery separator comprises the following steps:

[0012] Step 1: reacting 2,4,6-tris(4-aminophenyl)triazine and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde with pyruvic acid in a solvent to obtain a mixed solution A;

[0013] Step 2: The mixed solution A in step 1 is subjected to ultrasonic treatment, then rapidly frozen at low temperature and degassed by circulation, and then placed in an oven for reaction to obtain a yellow precipitate, which is then filtered, washed, and vacuum dried to obtain a covalent organic framework material;

[0014] Step 3: Grind the covalent organic framework material of step 2 and mix it with graphene, then dissolve it with methanol, and then perform ultrasonic treatment to obtain a mixed solution B, filter the mixed solution B onto a glass fiber diaphragm to obtain a filter membrane, dry and slice the filter membrane to obtain a high-performance zinc-iodine battery diaphragm.

[0015] Furthermore, in step 1, the molar ratio of 2,4,6-tris(4-aminophenyl)triazine, 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde and pyruvic acid is 1:1:3.3-3.7.

[0016] Furthermore, the molar ratio of the 2,4,6-tris(4-aminophenyl)triazine, 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde and pyruvic acid is 1:1:3.5.

[0017] Furthermore, in step 1, the molar amount of 2,4,6-tris(4-aminophenyl)triazine and the volume ratio of the solvent are 0.17mmol:2.5-4.0ml; the solvent is composed of o-dichlorobenzene and n-butanol, and the volume ratio of o-dichlorobenzene to n-butanol is 1-2:1-2.

[0018] Furthermore, in step 2, the cryogenic temperature is 77K, and the cyclic degassing condition is vacuum pumping-nitrogen filling, which is cycled at least 3 times, and the internal pressure is pumped to 10 -3 mbar.

[0019] Furthermore, in step 2, the washing solvents are acetone and methanol, and the washing is performed first with acetone and then with methanol; the reaction temperature in the oven is 80-160° C. and the reaction time is 48-96 hours; the vacuum drying temperature is 70-100° C. and the drying time is 4-6 hours.

[0020] Furthermore, in step 2, the reaction temperature in the oven is 100-120° C., and the reaction time is 48-72 hours. A reaction time that is too short will result in an incomplete reaction, and a reaction time that is too long will result in a waste of resources.

[0021] Furthermore, in step 3, the mass ratio of the covalent organic framework material to graphene is 2:0.8-1.4.

[0022] Furthermore, in step 3, the mass ratio of the covalent organic framework material to the graphene is 2:1.2. The mass ratio of the covalent organic framework material to the graphene determines the thickness of the prepared membrane.

[0023] Furthermore, in step 3, the ratio of the total mass of the covalent organic framework material and graphene to the volume of methanol is 20 mg:40-50 ml.

[0024] Furthermore, in step 3, the covalent organic framework material is ground into fine particles of 200-300 um.

[0025] Furthermore, in step 3, the ultrasonic treatment time is 10-20 minutes; the drying temperature is 40-70° C. and the drying time is 3-6 hours; and the slices are cut into discs with a diameter of 18 mm using a slicer.

[0026] The invention discloses a high-performance zinc-iodine battery separator prepared by the modification process.

[0027] Furthermore, the zinc-iodine battery separator has a pore size range of 1.2-1.8 nm and a thickness of 0.5-1.2 mm.

[0028] Application of the high-performance zinc-iodine battery separator of the present invention in the preparation of zinc-iodine batteries.

[0029] Furthermore, the zinc-iodine battery includes a positive electrode, a negative electrode, an electrolyte and a high-performance zinc-iodine battery separator; the positive electrode is an activated carbon cloth loaded with iodine; the negative electrode is a metal zinc foil or other zinc-containing metal alloy; and the electrolyte is a zinc salt aqueous solution.

[0030] Furthermore, the preparation process of the positive electrode of the iodine-loaded activated carbon cloth includes: mixing coconut shell carbon, carbon black and polyvinylidene fluoride adhesive in a mass ratio of 2:1-1.4:9-12, then adding solvent N-methylpyrrolidone, wherein the mass ratio of N-methylpyrrolidone to coconut shell carbon is 13-17:2, after stirring evenly, coating the slurry on carbon foil and drying at 50-70°C for 4-6 hours, and cutting the obtained carbon foil into discs with a diameter of 9 mm with a slicer, and then putting it into an open iodine absorption bottle, putting the iodine bottle into a 75°C oven for 2-3 days and taking it out to obtain the positive electrode sheet.

[0031] Furthermore, the negative electrode side of the zinc-iodine battery electrolyte is a 1-5M ZnSO4 aqueous solution, and the positive electrode side is a 1-5MZnSO4+0.4M ZnI mixed aqueous solution.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The high-performance zinc-iodine battery separator prepared by the present invention has excellent hydrophilicity and suitable pore size (1.2-1.8 nm), which promotes the 2+ The rapid transfer of iodine and the effective restriction of the shuttling of polyiodides by microporous confinement and the construction of chemically stable interfaces. Therefore, based on the synergistic effect of the above mechanisms, the high-performance zinc-iodine battery separator prepared by the present invention can effectively inhibit the shuttling of polyiodides, thereby significantly improving the battery performance and cycle life.

[0034] (2) Through the modification process of the present invention, the carboxylic acid groups rich in the zinc-iodine battery diaphragm can form a chemically stable interface on the surface of the diaphragm, slowing down the penetration rate of ions and improving the conductivity of the diaphragm, effectively preventing the unexpected reaction between iodine ions and zinc ions, thereby improving the cycle life and safety of the battery.

[0035] (3) The high-performance zinc-iodine battery separator of the present invention has shown significant advantages in the application of zinc-iodine batteries compared with glass fiber separators. These advantages are mainly reflected in indicators such as cycle performance and coulomb efficiency. In energy storage secondary batteries, the high-performance zinc-iodine battery separator shows great application prospects. -2 At a high current density of 1.34 W, its full cell provides a stable coulombic efficiency of over 90% and a cycle life of up to 800 h, indicating that this high-performance zinc-iodine battery separator has great potential in improving battery performance and extending service life.

[0036] (4) The high-performance zinc-iodine battery separator of the present invention adopts a simple one-step synthesis process, and the preparation method is simple. In addition, the cost of raw materials is low and it has environmental protection characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a reaction mechanism diagram of the COF#1 material prepared in Example 1 of the present invention.

[0038] Figure 2 This is a physical picture of the COF#1 material prepared in Example 1 of the present invention.

[0039] Figure 3 This is a physical picture of the COF#1 membrane prepared in Example 1 of the present invention.

[0040] Figure 4 This is the X-ray diffraction pattern of the COF#1 membrane prepared in Example 1 of the present invention.

[0041] Figure 5 This is a contact angle diagram of the COF#1 membrane prepared in Example 1 of the present invention.

[0042] Figure 6 The COF#1 membrane pair I3 prepared in Example 1 of the present invention - Ion permeability test results; Figure 6 (a) is the state diagram at the beginning of the test. Figure 6 (b) is the state diagram after standing for 1 h.

[0043] Figure 7 This is a scanning electron microscope image of the cross section corresponding to the COF#1 membrane prepared in Example 1 of the present invention.

[0044] Figure 8This is a comparison chart of electrochemical impedance of a full battery assembled with the COF#1 membrane prepared in Example 1 of the present invention and a blank commercial glass fiber membrane.

[0045] Fig. 9 The graph is a cyclic voltammetry curve at different scan rates of a full battery assembled with the COF#1 membrane prepared in Example 1 of the present invention.

[0046] Fig.10 The graph shows the cyclic voltammetry curves of a full cell assembled with a blank commercial glass fiber separator at different scan rates.

[0047] Fig.11 This is a comparison chart of the linear fitting of the peak current of the cyclic voltammetry curves of the full battery assembled with the COF#1 membrane prepared in Example 1 of the present invention and a blank commercial glass fiber membrane.

[0048] Fig.12 This is a cycle performance diagram of the zinc-iodine battery assembled with the COF#1 membrane prepared in Example 1 of the present invention.

[0049] Fig.13 The zinc-iodine battery assembled with the COF#2 diaphragm prepared in Comparative Example 1 of the present invention was 2 Scanning electron microscope image of zinc foil after 10 cycles under the same conditions. DETAILED DESCRIPTION

[0050] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0051] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0052] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0053] Embodiment 1

[0054] Step 1: 0.17 mmol 2,4,6-tris(4-aminophenyl)triazine, 0.17 mmol 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde, and 0.6 mmol pyruvic acid (60 μl) were added to a solvent consisting of 1.5 ml o-dichlorobenzene and 1.5 ml n-butanol to obtain a mixed solution A;

[0055] Step 2: The mixed solution A in step 1 was subjected to ultrasonic treatment for 20 minutes, and then rapidly frozen at 77K and degassed by vacuum-nitrogen filling cycles for 3 times. After thawing to room temperature, the mixed solution A was placed in a 120°C oven for 72 hours to obtain a yellow precipitate. The reaction mechanism is as follows: Figure 1As shown, according to the nitrogen adsorption isotherm curve, a yellow precipitate with a pore diameter of 1.7 nm was obtained. The yellow precipitate was first washed with 10 mL of acetone, then washed with 10 mL of methanol, and the washing cycle was repeated for multiple times, filtered, and then vacuum dried at 80°C for 6 hours to obtain a covalent organic framework material, such as Figure 2 As shown, it is recorded as COF#1.

[0056] Step 3: Grind the covalent organic framework material (COF#1) of step 2 for 10 minutes until the material is fine particles of 250 um, mix it with commercial graphene in a mass ratio of 2:1.2, and then dissolve it together in a beaker with methanol. The ratio of the total mass of the covalent organic framework material and graphene to the volume of methanol is 20 mg:40 mL. Then, ultrasonicate for 20 minutes to obtain a mixed solution B. Then, filter the mixed solution B onto a glass fiber diaphragm to obtain a filter membrane. Then, place the filter membrane in a 50°C vacuum drying oven and dry it for 6 hours. After drying, use a slicer to cut it into discs with a diameter of 18 mm, so as to obtain a zinc-iodine battery diaphragm, which is recorded as COF#1 diaphragm. The actual picture is as follows: Figure 3 shown.

[0057] The performance of the COF#1 membrane prepared in Example 1 of the present invention was tested, and the results are shown below.

[0058] like Figure 4 As shown, the figure gives the results of the X-ray diffraction pattern of COF#1 membrane, which shows that COF#1 membrane has good crystallinity.

[0059] like Figure 5 As shown in the figure, the contact angle of the COF#1 membrane is 83°. This shows that the prepared COF#1 membrane has good hydrophilicity, which is attributed to the rich carboxylic acid groups in the COF#1 membrane. The carboxylic acid groups can form a chemically stable interface on the membrane surface, slowing down the penetration rate of ions and improving the conductivity of the membrane, which effectively prevents the unexpected reaction between iodine ions and zinc ions, thereby improving the cycle life and safety of the battery.

[0060] like Figure 6 As shown, COF#1 membrane pair I3 - When testing ion permeability, Figure 6 As shown in (a), at the beginning of the test, the left side of the H-type glass battery is 1M ZnI2+0.1M I2 aqueous solution, the right side is aqueous solution, and the COF#1 separator is sandwiched in the middle; after standing for 1 hour, Figure 6 As shown in (b), the color change of the aqueous solution on the right is not obvious, which proves that the COF#1 membrane can effectively inhibit I3 - The shuttling of ions.

[0061] like Figure 7As shown, a scanning electron microscope morphology of the cross-section of the COF#1 diaphragm is given. It can be clearly seen that the lower substrate is glass fiber, the glass fiber structure as the supporting material is clearly visible, and the zinc-iodine battery diaphragm material is evenly covered on the surface of the glass fiber, which shows that the COF#1 diaphragm material can be well combined with the glass fiber to form a continuous and uniform coating. The material system shows good uniformity and consistency. This uniform coverage characteristic shows that the zinc-iodine battery diaphragm is very evenly distributed on the surface of the glass fiber, which helps to improve the overall performance of the material.

[0062] Example 2

[0063] The COF#1 diaphragm prepared in Example 1 was used to assemble a zinc-iodine battery into a full battery, denoted as COF@GR@GF; at the same time, the COF#1 diaphragm was replaced with a blank commercial glass fiber diaphragm for zinc-iodine battery assembly into a full battery as a comparison, denoted as GF, and the performance of the two was tested.

[0064] The tested zinc-iodine battery includes a positive electrode, a negative electrode, an electrolyte, and the zinc-iodine battery separator or a blank commercial glass fiber separator. The positive electrode is an activated carbon cloth loaded with iodine. The preparation process of the positive electrode includes: mixing coconut shell carbon, carbon black and polyvinylidene fluoride adhesive in a mass ratio of 2:1:10, then adding solvent N-methylpyrrolidone, wherein the mass ratio of N-methylpyrrolidone to coconut shell carbon is 15:2, stirring evenly, coating the slurry on carbon foil and drying at 60°C for 6 hours, and cutting the obtained carbon foil into discs with a diameter of 9 mm with a slicer, and then putting it into an open iodine absorption bottle, and putting the iodine bottle into a 75°C oven for 3 days to obtain the positive electrode sheet;

[0065] The negative electrode is a metal zinc foil;

[0066] The negative electrode side of the zinc-iodine battery electrolyte is 400ul of a 2M ZnSO4 aqueous solution; the positive electrode side is 400ul of a mixed aqueous solution consisting of 2MZnSO4+0.4M ZnI.

[0067] Figure 8 The electrochemical impedance comparison diagram of the zinc-iodine full cell assembled with COF#1 membrane and blank commercial glass fiber membrane is given. The results show that in the full cell, the COF#1 membrane of the present invention has a smaller charge transfer resistance, indicating that the introduction of the covalent organic framework material prepared by the present invention significantly improves the charge transfer kinetics, which is of great significance for improving the performance of the full cell.

[0068] Fig. 9 and Fig.10 The cyclic voltammetry curves of the zinc-iodine full cell assembled with COF#1 membrane and blank commercial glass fiber membrane are given respectively. Fig.11A comparison chart of the peak current linear fitting of the cyclic voltammetry curves of the two assembled into a zinc-iodine full battery is given. Fig. 9 and Fig.10 It can be seen that compared with the blank commercial glass fiber separator, the COF#1 separator of the present invention exhibits a higher peak current and a smaller polarization potential, which indicates that its electrochemical performance is superior. Fig.10 The linear fitting results show that COF#1 membrane has a larger slope, indicating that the Zn 2+ The mobility of COF#1 membrane of the present invention is significantly increased. 2+ The mobility is 2.3×10 -10 , while the blank commercial glass fiber separator has Zn 2+ The mobility is 9.9×10 -11 Therefore, the use of the covalent organic framework material of the present invention in preparing zinc-iodine battery separators can significantly increase the Zn 2+ Mobility, speed up I2 / I - The redox kinetics process is favorable for the zinc deposition / stripping behavior.

[0069] Fig.12 The cycling performance of the zinc-iodine full battery assembled with COF#1 separator and blank commercial glass fiber separator is given. The results show that compared with the blank commercial glass fiber separator, COF#1 separator performs well and exhibits excellent cycling stability. -2 At a current density of 1.5 Å, the full cell provides a stable coulombic efficiency of over 90% and can be cycled continuously for 800 hours.

[0070] Comparative Example 1

[0071] This comparative example is compared with Example 1: the pyruvic acid in step 1 is replaced with acetic acid to prepare a high-performance zinc-iodine battery separator, and the rest is the same as Example 1.

[0072] The modification process of the high-performance zinc-iodine battery separator of this comparative example comprises the following steps:

[0073] Step 1: 0.17 mmol 2,4,6-tris(4-aminophenyl)triazine, 0.17 mmol 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde, and 0.6 mmol acetic acid (60 μl) were added to a solvent consisting of 1.5 ml o-dichlorobenzene and 1.5 ml n-butanol to obtain a mixed solution A;

[0074] Step 2: The mixed solution A in step 1 was ultrasonically treated for 20 minutes, and then quickly frozen at 77K and degassed by vacuum-nitrogen filling for 3 times. After thawing to room temperature, it was placed in a 120°C oven for 72 hours to obtain a precipitate, which was first washed with 10 mL of acetone, then washed with 10 mL of methanol, and washed several times in this cycle, filtered, and then vacuum dried at 80°C for 6 hours to obtain a covalent organic framework material, recorded as COF#2;

[0075] Step 3: Grind the covalent organic framework material (COF#2) for 10 minutes until the material is fine particles of 250 um, mix it with commercial graphene in a mass ratio of 2:1.2, and then dissolve it together with methanol in a beaker. The ratio of the total mass of the covalent organic framework material and graphene to the volume of methanol is 20 mg:40 mL. Then, ultrasonicate for 20 minutes to obtain a mixed solution B. Then, filter the mixed solution B onto a glass fiber diaphragm to obtain a filter membrane. Then, place the filter membrane in a 50°C vacuum drying oven and dry it for 6 hours. After drying, use a slicer to cut it into discs with a diameter of 18 mm to obtain a zinc-iodine battery diaphragm.

[0076] like Fig.13 As shown, the zinc-iodine battery separator prepared in this comparative example was used to assemble a zinc-iodine battery, and then 2 After 10 cycles under the same conditions, the zinc foil was scanned by electron microscope. As can be seen from the figure, there are a large number of zinc dendrites and zinc foil collapse on the surface of the negative zinc foil, which leads to poor battery cycle performance and low coulomb efficiency. The results show that the present invention improves the performance of the zinc-iodine battery diaphragm by mixing 2,4,6-tris(4-aminophenyl)triazine and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde in an appropriate amount of acetone, thereby effectively improving the performance of the assembled zinc-iodine battery.

[0077] Comparative Example 2

[0078] This comparative example is compared with Example 1: This comparative example does not add graphene to prepare the zinc-iodine battery separator, and the rest is the same as Example 1.

[0079] The modification process of the high-performance zinc-iodine battery separator of this comparative example comprises the following steps:

[0080] Step 1: 0.17 mmol 2,4,6-tris(4-aminophenyl)triazine, 0.17 mmol 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde, and 0.6 mmol pyruvic acid (60 μl) were added to a solvent consisting of 1.5 ml o-dichlorobenzene and 1.5 ml n-butanol to obtain a mixed solution A;

[0081] Step 2: The mixed solution A in step 1 was subjected to ultrasonic treatment for 20 minutes, and then rapidly frozen at 77K and degassed by vacuum-nitrogen filling cycles for 3 times. After thawing to room temperature, the mixed solution A was placed in a 120°C oven for 72 hours to obtain a yellow precipitate. The reaction mechanism is as follows: Figure 1 As shown, according to the nitrogen adsorption isotherm curve, a yellow precipitate with a pore diameter of 1.7 nm was obtained. The yellow precipitate was first washed with 10 mL of acetone, then washed with 10 mL of methanol, and this was repeated for multiple washings. The precipitate was filtered and then vacuum dried at 80°C for 6 hours to obtain a covalent organic framework material, which was recorded as COF#1.

[0082] Step 3: Grind the covalent organic framework material (COF#1) of step 2 for 10 minutes until the material is fine particles of 250 um, and then dissolve it in a beaker with methanol, wherein the ratio of the total mass of the covalent organic framework material to the volume of methanol is 20 mg:40 mL, and then perform ultrasound for 20 minutes to obtain a mixed solution B, and then filter the mixed solution B onto a glass fiber diaphragm to obtain a filter membrane, and then place the filter membrane in a 50°C vacuum drying oven and dry it for 6 hours. After drying, use a slicer to cut it into discs with a diameter of 18 mm to obtain a zinc-iodine battery diaphragm.

[0083] Compared with Example 1, the conductivity and mechanical stability of the zinc-iodine battery separator prepared in this comparative example are poor, indicating that the lack of graphene leads to a decrease in the conductivity of the separator, affecting the battery's charge and discharge efficiency and cycle life, thereby reducing the battery's performance.

[0084] In addition, when the zinc-iodine battery separator prepared in this comparative example is used in the assembly of zinc-iodine batteries, the performance and safety of the zinc-iodine batteries are significantly reduced. This shows that not adding graphene will also increase the internal resistance of the battery, increase the energy loss during the battery discharge process, and reduce the power performance of the battery; at the same time, the mechanical strength and stability of the separator are weakened, and perforation or damage is likely to occur, affecting the safety of the battery.

[0085] Therefore, adding a reasonable proportion of graphene in the process of preparing zinc-iodine battery separators can effectively improve the conductivity and mechanical stability of the separators, and improve the performance and safety of zinc-iodine batteries.

[0086] Example 3

[0087] Step 1: 0.17 mmol of 2,4,6-tris(4-aminophenyl)triazine, 0.17 mmol of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde and 0.63 mmol of pyruvic acid are added to a solvent consisting of 1.0 ml of o-dichlorobenzene and 2.0 ml of n-butanol to obtain a mixed solution A;

[0088] Step 2: The mixed solution A in step 1 was subjected to ultrasonic treatment for 20 minutes, and then rapidly frozen at 77K and degassed by vacuum-nitrogen cycle for 3 times. After thawing to room temperature, the mixed solution A was placed in an oven at 100°C for 86 hours to obtain a yellow precipitate. The reaction mechanism is as follows: Figure 1 As shown, according to the nitrogen adsorption isotherm curve, a yellow precipitate with a pore diameter of 1.7 nm was obtained. The yellow precipitate was first washed with 10 mL of acetone, then washed with 10 mL of methanol, and this was repeated for multiple washings. The precipitate was filtered and then vacuum dried at 70°C for 6 hours to obtain a covalent organic framework material, which was recorded as COF#3.

[0089] Step 3: Grind the covalent organic framework material (COF#3) of step 2 for 10 minutes until the material is fine particles of 250 um, mix it with commercial graphene in a mass ratio of 2:1.4, and then dissolve it together with methanol in a beaker, the ratio of the total mass of the covalent organic framework material and graphene to the volume of methanol is 20 mg:50 mL, then perform ultrasound for 15 minutes to obtain a mixed solution B, and then filter the mixed solution B onto a glass fiber diaphragm to obtain a filter membrane, and then place the filter membrane in a 60°C vacuum drying oven to dry for 4 hours. After drying, use a slicer to cut it into discs with a diameter of 18 mm to obtain a zinc-iodine battery diaphragm.

[0090] Example 4

[0091] Step 1: 2,4,6-tris(4-aminophenyl)triazine, 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde and 0.56 mmol of pyruvic acid were added to a solvent consisting of 2.0 ml of o-dichlorobenzene and 1.0 ml of n-butanol to obtain a mixed solution A;

[0092] Step 2: After ultrasonic treatment of the mixed solution A in step 1 for 20 minutes, it was quickly frozen at a low temperature of 77K and degassed by vacuum-nitrogen filling cycles for 3 times. After thawing to room temperature, it was placed in a 160°C oven and reacted for 54 hours to obtain a yellow precipitate. According to the nitrogen adsorption isotherm curve, a yellow precipitate with a pore diameter of 1.7 nm was obtained. The yellow precipitate was first washed with 10 mL of acetone and then with 10 mL of methanol. The washing cycle was repeated several times, filtered, and then vacuum dried at 100°C for 4 hours to obtain a covalent organic framework material, recorded as COF#4.

[0093] Step 3: Grind the covalent organic framework material (COF#4) of step 2 for 10 minutes until the material is fine particles of 300um, mix it with commercial graphene in a mass ratio of 2:0.8, and then dissolve it together with methanol in a beaker, the ratio of the total mass of the covalent organic framework material and graphene to the volume of methanol is 20mg:45mL, then perform ultrasound for 10 minutes to obtain a mixed solution B, and then filter the mixed solution B onto a glass fiber diaphragm to obtain a filter membrane, and then place the filter membrane in a 40°C vacuum drying oven to dry for 5 hours. After drying, use a slicer to cut it into discs with a diameter of 18mm to obtain a zinc-iodine battery diaphragm.

[0094] Through experiments, it was found that the zinc-iodine battery separators prepared in Examples 3 and 4 of the present invention also have good performance compared with Example 1; in addition, the zinc-iodine battery separators prepared in Examples 3 and 4 were used to assemble zinc-iodine batteries and then their performance was tested. The zinc-iodine batteries had high conductivity and mechanical stability, and also showed excellent performance.

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A modification process for a high-performance zinc-iodine battery separator, characterized in that: The following steps are involved: Step 1: reacting 2,4,6-tris(4-aminophenyl)triazine and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde with pyruvic acid in a solvent to obtain a mixed solution A; Step 2: The mixed solution A in step 1 is subjected to ultrasonic treatment, then rapidly frozen at low temperature and degassed by circulation, and then placed in an oven for reaction to obtain a yellow precipitate, which is then filtered, washed, and vacuum dried to obtain a covalent organic framework material; Step 3: Grind the covalent organic framework material of step 2 and mix it with graphene, then dissolve it with methanol, and then perform ultrasonic treatment to obtain a mixed solution B, filter the mixed solution B onto a glass fiber diaphragm to obtain a filter membrane, dry and slice the filter membrane to obtain a high-performance zinc-iodine battery diaphragm.

2. The modification process of the high performance zinc-iodine battery separator according to claim 1, characterized in that: In step 1, the molar ratio of 2,4,6-tris(4-aminophenyl)triazine, 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde and pyruvic acid is 1:1:3.3-3.

7.

3. The modification process of the high performance zinc-iodine battery separator according to claim 1, characterized in that: In step 1, the molar amount of 2,4,6-tris(4-aminophenyl)triazine and the volume ratio of the solvent are 0.17mmol:2.5-4.0ml; the solvent is composed of o-dichlorobenzene and n-butanol, and the volume ratio of o-dichlorobenzene to n-butanol is 1-2:1-2.

4. The modification process of the high performance zinc-iodine battery separator according to claim 1, characterized in that: In step 2, the washing solvents are acetone and methanol, and the washing is first performed with acetone and then with methanol; the reaction temperature in the oven is 80-160° C. and the reaction time is 48-96 hours; the vacuum drying temperature is 70-100° C. and the drying time is 4-6 hours.

5. The modification process of the high performance zinc-iodine battery separator according to claim 1, characterized in that: In step 3, the mass ratio of the covalent organic framework material and graphene is 2:0.8-1.4; the ratio of the total mass of the covalent organic framework material and graphene to the volume of methanol is 20 mg:40-50 ml.

6. The modification process of the high performance zinc-iodine battery separator according to claim 1, characterized in that: In step 3, the ultrasonic treatment time is 10-20 minutes; the drying temperature is 40-70° C. and the drying time is 3-6 hours; and the slices are cut into discs with a diameter of 18 mm using a slicer.

7. A high-performance zinc-iodine battery separator prepared by the modification process described in any one of claims 1 to 6.

8. The high performance zinc-iodine battery separator according to claim 7, characterized in that: The zinc-iodine battery diaphragm has a pore size of 1.2-1.8 nm and a thickness of 0.5-1.2 mm.

9. Use of the high-performance zinc-iodine battery separator prepared by the modification process described in any one of claims 1 to 6 or the high-performance zinc-iodine battery separator described in any one of claims 7 to 8 in the preparation of zinc-iodine batteries.

10. The use according to claim 9, characterized in that: The zinc-iodine battery comprises a positive electrode, a negative electrode, an electrolyte and a high-performance zinc-iodine battery separator; the positive electrode is an activated carbon cloth loaded with iodine; the negative electrode is a metal zinc foil or other metal alloy containing zinc; and the electrolyte is a zinc salt aqueous solution.

Citation Information

Patent Citations

  • Covalent organic framework material containing quinoline carboxylic acid groups as well as preparation method and application thereof

    CN112044402A

  • Diaphragm material for lithium-sulfur battery as well as preparation method and application of diaphragm material

    CN117039325A

  • Preparation method and application of covalent organic framework self-supporting diaphragm

    CN117878528A

  • Preparation of paper-based covalent organic framework chip and application of paper-based covalent organic framework chip in preparation of hydrogen peroxide

    CN118059939A

  • Functional modified phosphazene type covalent organic framework material as well as preparation method and application thereof

    CN118440333A